2016
DOI: 10.1371/journal.pone.0149664
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Influence of Nonadaptive Evolution on Primate Color Vision

Abstract: Color vision in primates is variable across species, and it represents a rare trait in which the genetic mechanisms underlying phenotypic variation are fairly well-understood. Research on primate color vision has largely focused on adaptive explanations for observed variation, but it remains unclear why some species have trichromatic or polymorphic color vision while others are red-green color blind. Lemurs, in particular, are highly variable. While some species are polymorphic, many closely-related species ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…Yet other day-active lemurs appear to have a single opsin allele and are strictly dichromatic [9][10][11]. There is some behavioural evidence linking differences in opsin gene variation to differences in colour vision phenotypes among lemurs [8,12], and it has been suggested that this variation might be influenced by ecological differences, including the degree of diurnal behaviour [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet other day-active lemurs appear to have a single opsin allele and are strictly dichromatic [9][10][11]. There is some behavioural evidence linking differences in opsin gene variation to differences in colour vision phenotypes among lemurs [8,12], and it has been suggested that this variation might be influenced by ecological differences, including the degree of diurnal behaviour [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is some behavioural evidence linking differences in opsin gene variation to differences in colour vision phenotypes among lemurs [8,12], and it has been suggested that this variation might be influenced by ecological differences, including the degree of diurnal behaviour [10]. This hypothesis has been difficult to evaluate, however, because X-linked opsin data are only available for a few lemur taxa [6][7][8][9][10][11]. To help fill this gap, we provide the first comprehensive examination of X-linked opsin variation across members of the lemur family Indriidae.…”
Section: Introductionmentioning
confidence: 99%
“…Although polymorphism has been reported in just four species, it is possible that this may be an underestimate of the number of trichromatic prosimian species since many of the studies have been restricted to small cohorts of animals. However, a recent study using a large sample group of the red-bellied lemurs (Eulemur rubriventer) showed that this species has a 100% frequency of the L allele with Thr at site 285, probably due to a genetic bottle neck event in the studied population (Jacobs and Bradley, 2016). Indeed this same group later demonstrated that amongst lemur species, the presence of M or L pigments is highly variable .…”
Section: Trichromacy In Prosimiansmentioning
confidence: 96%
“…However, it is important to notice that, in many cases, different combinations of residues across the three sites ( (Jacobs and Deegan, 2003a). In the other two families that form the New World monkey parvorder, Data taken from Mollon et al (1984), Travis et al (1988), Boissinot et al (1998), Tan and Li (1999), Jacobs and Deegan (2001, 2003a,b, 2005, Saito et al (2004), Talebi et al (2006), Veilleux and Bolnick (2009), Bunce et al (2011), Corso et al (2016, and Jacobs and Bradley (2016).…”
Section: Trichromacy In New World Primatesmentioning
confidence: 99%
“…Very little work has examined the ecology of color vision in trichromat or potentially trichromat lemur populations343536. Although trichromacy among lemurs may be functionally different from trichromacy in platyrrhines due to lower retinal cone density37 and lower visual acuity3839, experimental evidence suggests that trichromacy can influence lemur foraging behavior40.…”
mentioning
confidence: 99%